AUTOMATED ELECTRICITY MONITORING AND REPORTING SYSTEM - Umiten, Niña Nicole A. (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
In traditional power outage reporting systems, consumers are often responsible for reporting the issue, which can cause delays in resolving the problem as they may not know the full extent of the outage. This research aims to create a device designed to continuously monitor electricity and notify providers of outages. Due to its portability and low power consumption, the researchers utilized the Arduino Nano. In addition to this, they incorporated the Split Core AC Transformer Module, the ZMPT ACS power line sensor, and an I2C 20x4 LCD screen. Furthermore, a SIM GSM Module was employed to facilitate communication with a pre-registered mobile number. To determine the functionality a series of tests were conducted. The device was tested by turning the power supply off three times for determining the speed of power detection. Then it was turned back on, and continuously monitored the electricity for three minutes. The SMS alert system was also tested by simulating a power outage and verifying that it sent a text message to the pre-registered number with the message "Power Outage Detected!!!" In addition, the LCD displayed "Status: Failure!" to indicate the power outage It can detect a power outage at an average of 8.53 seconds, while 6.64 seconds to detect power restoration.  The prototype can also successfully display its status on the LCD screen, as well as send an SMS to the preregistered mobile number. The device prototype is functional in terms of continuous electricity monitoring, and power outage detection.